Exercisers' Affective and Enjoyment Responses: A Meta-Analytic and Meta-Regression Review. Issue 5 (October 2021) - Tavares, Vagner Deuel de Oliveira; Schuch, Felipe Barreto; Tempest, Gavin; Parfitt, Gaynor; Oliveira Neto, Leônidas; Galvão-Coelho, Nicole Leite; Hackett, Daniel
Affective responses and enjoyment of exercise mediate exercise adherence, but previous research findings have failed to examine nuances that may moderate this relationship. We examined the effects of exercise on affective and enjoyment responses during and post exercise through a systematic literature review and meta-regression analysis. We searched major databases up to July 9, 2020 for studies evaluating healthy adults' acute and chronic responses to exercise, using either of The Feeling Scale or Physical Activity Enjoyment Scales. We calculated effect size (ES) values of 20 unique studies (397 participants; 40% females) as standardized differences in the means and expressed them as Hedges' g, together with the 95% confidence interval (95%CI). Among acute studies examining affective responses, we found a greater positive effect post exercise for continuous training (CT) compared to high intensity interval training (HIIT) ( g = −0.61; 95%CI = −1.11, −0.10; p < .018), but there was no significant difference between these modes for effects during exercise. Subgroup analyses revealed that moderate, and not high intensity, CT, compared to HIIT, resulted in significantly greater positive affective responses ( g = −1.09; 95%CI = −1.88, −0.30; p < .006). In contrast, enjoyment was greater for HIIT, compared to CT ( g = 0.75; 95%CI = 0.17, −1.13; p = .010), but CT intensity did not influence this result. Among chronic studies, there was greater enjoyment following HIIT compared to CT, but these studies were too few to permit meta-analysis. We concluded that an acute bout of moderate intensity CT is more pleasurable, when measured post exercise than HIIT, but enjoyment is greater following HIIT, perhaps due to an interaction between effort, discomfort, time efficiency and constantly changing stimuli.